Importance Of Implementing Visual Aids in Teaching Esp Students - Muwsa Narimbetov Eliwbay uli; Elmira Azerbaeva Muratbaevna (Genius Journals, 2022)
This article informs about the importance of using visual aids in teaching ESP students. Moreover, it contains practical experiments on conducting lessons with and without visual aids to the biology students of Karakalpak higher education.
Keywords: ESP; visual aids; authentic materials; biology